2015
DOI: 10.1111/jvim.13645
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Findings of 140 Bile Samples from Dogs and Cats and Associated Clinical Pathological Data

Abstract: BackgroundCholecystocentesis can be part of the diagnostic workup of hepatobiliary disease in small animals, but literature on cytological evaluation of bile is scant.ObjectivesTo determine the diagnostic utility of cytological assessment of bile aspirates.AnimalsFifty‐six and 78 client‐owned dogs and cats, respectively, with bile collected by cholecystocentesis and submitted to our diagnostic laboratory between 1999 and 2014.MethodsRetrospective study describing cytological findings of bile, concurrent bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 19 publications
8
46
0
Order By: Relevance
“…A third study of bile cytology and culture in cats and dogs with suspected hepatobiliary disease found that in 30% of canine cases, infectious agents were involved. E. coli and Enterococcus species were most common, as in prior reports . Only 4 of 6 dogs had gallbladder histopathology confirming a diagnosis of cholecystitis, whereas 3 dogs had cholangiohepatitis.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…A third study of bile cytology and culture in cats and dogs with suspected hepatobiliary disease found that in 30% of canine cases, infectious agents were involved. E. coli and Enterococcus species were most common, as in prior reports . Only 4 of 6 dogs had gallbladder histopathology confirming a diagnosis of cholecystitis, whereas 3 dogs had cholangiohepatitis.…”
supporting
confidence: 56%
“…Only 4 of 6 dogs had gallbladder histopathology confirming a diagnosis of cholecystitis, whereas 3 dogs had cholangiohepatitis. Concurrent diseases identified in dogs with biliary inflammation or infection included hepatopathies, pancreatic disease, and inflammatory bowel disease …”
mentioning
confidence: 99%
“…Generally, identification of concurrent bacterial infection of the bile, GB mucosa or liver in cases of GBM is challenging. Ultrasound-guided percutaneous cholecystocentesis is a common and typically safe procedure for the collection of bile for the purposes of cytologic evaluation and culture (Uno et al 2009, Peters et al 2016, Schiborra et al 2017. However, biliary mucocele is considered by many to be a contraindication to cholecystocentesis as the potential for GB necrosis secondary to GBM makes rupture of the biliary tract possible (Nyland et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Peters et al . () in their paper on the diagnostic utility of cytological assessment of bile aspirates describe that of 140 patients, complications occurred in 4 dogs and 1 cat. Only three of these occurred after PUC.…”
Section: Discussionmentioning
confidence: 99%
“…, Peters et al . ). Therefore, the aim of this study was to evaluate complications in cases presented for PUC, and to describe and determine the incidence of encountered complications.…”
Section: Introductionmentioning
confidence: 97%